Synthesis, properties, and applications of an anionic–nonionic Gemini surfactant for highly efficient remediation of perchloroethylene-contaminated aquifers. (20th January 2022) - Yao, Yu; Fu, Yufeng; Zhang, Li; Xuan, Lishuang; Qin, Chuanyu
Abstract: Monomeric surfactants are currently used for the remediation of dense non-aqueous phase liquid-contaminated groundwater. However, they result in low remediation efficiency because of their high adsorption loss and low temperature and salt resistance. In this study, a novel and green Gemini surfactant, SNE(10)SID (sodium nonylphenol ethoxylate (10) sulfoitaconate diester), was synthesized for subsurface environment characteristics through esterification and sulfonation. This surfactant consisted of two long and straight hydrophobic chains, two selfsame non-ionic portions, and two anionic moieties covalently connected to each other by an itaconic acid spacer. The critical micelle concentration was ∼10 −4  M. The interfacial tension between SNE(10)SID and perchloroethylene (PCE) was significantly low, and the value was found to be 1.0 mN/m. SNE(10)SID exhibited excellent activity under conditions of low temperature and in high salt systems. The solubility of PCE was up to 8863 mg/L in a 4 wt% SNE(10)SID solution, which was two orders of magnitude higher than the solubility recorded in pure water. SNE(10)SID exhibited a low adsorption loss (only 0.8 mg/g at a concentration of 2 g/L in medium sand). The PCE desorption ability of the surfactant was far significantly higher than the PCE desorption abilities of other monomeric surfactants in various aquifer media. Under conditions of dynamic flushing, the low-viscosity SNE(10)SID solution exhibited excellent remediation ability when PCE-contaminated simulated aquifers were used for the studies. The total PCE removal rate reached was 87.5% after the flushing of 10 pore volumes. These results revealed that SNE(10)SID was an excellent surfactant that could be used to realize efficient aquifer remediation. Graphical abstract: Image 1 Highlights: The anionic-nonionic Gemini surfactant SNE(10)SID was synthesized. SNE(10)SID exhibited high surface activity under aquifer conditions. SNE(10)SID exhibited excellent solubilization and desorption ability. SNE(10)SID exhibited effective PCE removal ability in simulated groundwater. SNE(10)SID showed application potential for DNAPL contaminated aquifers.